Neurotransmitter amino acid-oxobenzo [f]benzopyran conjugates: synthesis and photorelease studies - Fernandes, Maria J. G. (2008)
A series of fluorescent conjugates of neurotransmitter amino acids, such as P-alanine, tyrosine, 3,4-dihydroxyplienylalanine (DOPA) and glutamic acid, were prepared by reaction with a suitable fluorophore, namely 1-chloromethyl-9-methoxy-3-oxo-3H-benzo[f]benzopyran. The photophysical properties of the resulting ester bioconjugates were evaluated as well as the stability to photolysis at different wavelengths of irradiation (250, 300, 350 and 419 nm).